KETAHANAN BEBERAPA GENOTIPE PADI LOKAL KAMBA TERHADAP PENYAKIT TUNGRO - Ahmad Hamdani Hamzah; Irwan Lakani; Mohammad Yunus (Agroland: Jurnal Ilmu-ilmu Pertanian, 2015)
The aim of this rescend is to determined level of resistance of some local paddy kamba genotypes against tungro disease. The results of reased are used to complete the description of the local paddy genotypes Kamba according to Standard Evaluation System for Rice from IRRI. The study wes conducted in Screen House of Plant Pests and Diseases Laboratory Faculty of Agriculture, Tadulako University, Palu. The research method refers to the method developed by Plant Research Tungro Station Lanrang sand selebes. Four local paddy genotypes used were Kamba tomado, Kamba kolori, Kamba bulili, Kamba Wuasa, as a compared with rice suscepbtible varieties TN1, and resistant Utri Merah to tungro. Each type of paddy genotipes used are 20 plants, so that ther are 120 population plants. The results showed in the four genotypes tested, the highest incidence rate of disease is Kamba Wuasa (4.8%) the lowest Whereas the Kamba bulili (1.1%). According to criteria of evaluasi system for rice standar , four local paddy genotipes kamba are tester showwed resistence and moderat resistence to agains tungro disiase. With value of disiase index from 1,2 to 4,8. Key words : Paddy local, kamba resilience genotype, standard evaluation system for rice, tungro disease.